EFFECT OF ADDITION OF MEAT FISH PATIN (Pangasius hypopthalmus) RENGGINANG PROCESSING OF CASSAVA (Manihot esculenta C) ASSESSMENT OF ORGANOLEPTIC - Judith, Febrina; Buchari, Dewita; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aims to determine the effect of meat catfish (Pangasius hypopthalmus) on rengginang processing of cassava (Manihot esculenta C) to the organoleptic assessment. The method used is experiment with a completely randomized design consisting of 4 levels of treatment that Ro (without the addition of meat catfish), R1 (75 g of meat catfish), R2 (100 g of meat catfish), R3 (125 g of meat catfish). Catfish fillets are weeded and then ground and washed and grated cassava then drained. Meat that has been creamed catfish mixed with herbs and cassava according to treatment and stir until blended. The dough is mixed with tapioca flour until fused. The dough is molded and steamed for 12 minutes and then dried for 1-2 days in a dryer. Rengginang dried and then fried. The parameters tested is organoleptic and chemical. The results showed that the organoleptic and chemical based rengginang meat catfish are preferred by consumers and good quality is R1 treatment with the addition of 75 g of meat catfish with such criteria (intact, neat, clean, average thickness, brownish yellow color); aroma (little fish); texture (crunchy); and taste (little fish); with a water content of 1.87%, 21.87% protein content, fat content of 33.34% and ash content of 1.68%.Keyword: meat catfish, rengginang.